Synaptic Spinules in the Olfactory Circuit of Drosophila melanogaster - Gruber, Lydia; Rybak, Jürgen; Hansson, Bill S.; Cantera, Rafael (Frontiers in Cellular Neuroscience, 2018)
ABSTRACT Here we report on ultrastructural features of brain synapses in the fly Drosophila melanogaster and outline a perspective for the study of their functional significance. Images taken with the aid of focused ion beam-scanning electron microscopy at 20 nm intervals across olfactory glomerulus DA2 revealed that some synaptic boutons are penetrated by protrusions emanating from other neurons. Similar structures in the brain of mammals are known as synaptic spinules. A survey with transmission electron microscopy disclosed that these structures are frequent throughout the antennal lobe. Detailed neuronal tracings revealed that spinules are formed by all three major types of neurons innervating glomerulus DA2 but the olfactory sensory neurons receive significantly more spinules than other olfactory neurons. Double-membrane vesicles that appear to represent material that has pinched-off from spinules are also most abundant in presynaptic boutons of olfactory sensory neurons. Inside the host neuron, a close association was observed between spinules, the endoplasmic reticulum and mitochondria. We propose that by releasing material into the host neuron, through a process triggered by synaptic activity and analogous to axonal pruning, synaptic spinules could function as a mechanism for synapse tagging, synaptic remodeling and neural plasticity. Future directions of experimental work to investigate this theory are proposed.